Propranolol Oral Treatment for Infantile Hemangioma : A Systematic Review - Aulia Nissa Rizky Hariyono; Ratih Pramuningtyas; Zhela Fatin Fatiha; Ayu Mayangsari; Tia Mella Citra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The most common benign tumor in infants is infantile hemangioma. Propranolol is often used as a treatment in patients with IHs. Efficacy and side effects of oral propranolol are considered important to be systematically reviewed in the management of IH. We searched Google Scholar, Pubmed, Garuda, and Science Direct. The articles matched with the restriction criteria then screened using the PRISMA method. The quality of the articles is tested using GRADE method. Total of 4 of 6289 articles recorded at the identification stage according to the inclusion criteria, 452 patients were treated with oral propranolol. All four articles were randomized clinical trials. Treatment is given at 0.3 month to 15 years of age, the dose given is 1-3 mg/kg/day. The primary end point was performed at week 24. The most common side effect is sleeping disorder (n=85). Serious side effects (Hypotension, bronchospasm, bradycardia, hypoglycemia) were managed by decreasing doses or temporary/permanent discontinuation of oral propranolol. Oral propranolol can be used with good efficacy. Monitor before and during treatment is assessed appropriately to reduce side effect.